Analisis Informasi Pertanggungjawaban Keuangan Untuk Penyusunan Anggaran (Studi pada CV. Sinar Harapan di Kota Watansoppeng) - Rukmana Sari (Economics and Digital Business Review, 2024)
This research is concerned with the analysis of financial accountability information for budget preparation (study on CV Sinar Harapan in Watansoppeng City). There are two data sources in this study, namely primary data and secondary data. There are two types of data in this study, namely quantitative data types and qualitative data types. To obtain data that is relevant to the issues discussed, the research uses the following data collection methods, namely literature study, documentation study, interview study, observation, and internet searching. Data analysis in qualitative research moves deductively, i.e. categorised facts or data towards a higher level of abstraction, synthesising and developing theories when necessary. After the data is collected, it is then analysed to describe and draw conclusions regarding the analysis of responsibility accounting information for budget preparation (study on CV. Sinar Harapan in Watansoppeng City). The results of this research indicate that the preparation of the company's budget carried out by CV Sinar Harapan Watansoppeng City has not fully used the accountability financial information system optimally. Especially in cost centres such as production costs, administrative and general costs. We can see this in the 2022 budget preparation plan which does not consider the 2021 budget realisation. Then in the optimal application of the accountability financial information system in budgeting at CV Sinar Harapan Watansoppeng City, it should meet the five determining conditions for the application of responsibility accounting, namely, (a) An organisation consisting of responsibility centres and there is decentralisation in it. (b) The cost budget is prepared according to the responsibility centre. (c) Classification of costs in accordance with the control of costs by responsibility centre management. (d) Cost accounting system in accordance with the organisational structure. (e) Cost reporting system to the responsible manager.